2016
DOI: 10.1111/jfb.12878
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of yellownose skate Zearaja chilensis, a top predator in the south‐western Atlantic Ocean

Abstract: The diet and trophic level (TL ) of the yellownose skate Zearaja chilensis in the south-western Atlantic Ocean (35°-54° S), and how these varied in relation to body size, sex, maturity stage, depth and region were determined by analysis of stomach contents. From 776 specimens analysed, 671 (86·5%) ranging from 180 to 1190 mm total length (LT ) had prey in their stomachs. The diet was dominated by fishes, mainly the notothenioid Patagonotothen ramsayi and the Argentine hake Merluccius hubbsi. The consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Information about how teeth vary with ontogeny is not available, although this will impact the usefulness of row count for taxonomic purposes. Sexually dimorphic dentition has been reported in Z. chilensis, with sharp and conical (spike-shaped) teeth in mature male skates, while females have blunt 'oval shaped' teeth (Leible, 1987;Sáez & Lamilla, 1997;Belleggia et al, 2016). Such sexual dimorphism dentition was hypothesised to correlate with different diets between the sexes in batoids (Feduccia & Slaughter, 1974), but has since shown to facilitate the male grasp of the female pectoral fins to aid in the act of copulation (McEachran, 1977;Gutteridge & Bennett, 2014).…”
Section: Dentitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Information about how teeth vary with ontogeny is not available, although this will impact the usefulness of row count for taxonomic purposes. Sexually dimorphic dentition has been reported in Z. chilensis, with sharp and conical (spike-shaped) teeth in mature male skates, while females have blunt 'oval shaped' teeth (Leible, 1987;Sáez & Lamilla, 1997;Belleggia et al, 2016). Such sexual dimorphism dentition was hypothesised to correlate with different diets between the sexes in batoids (Feduccia & Slaughter, 1974), but has since shown to facilitate the male grasp of the female pectoral fins to aid in the act of copulation (McEachran, 1977;Gutteridge & Bennett, 2014).…”
Section: Dentitionmentioning
confidence: 99%
“…For Z. chilensis it has been shown that crustaceans form the main prey category for skates of < 50 cm LT (Bahamonde, 1953;De Buen, 1959;Sánchez & Prenski, 1996;Koen Alonso et al, 2001), which would result in a trophic level of about 3.5. However, Belleggia et al (2016) (Sánchez & Prenski, 1996;García de la Rosa, 1998;Lucifora et al, 2000;Paesch, 2000;Koen Alonso et al, 2001;Sánchez & Mabragaña, 2002;Belleggia et al, 2016), confirming their ecological role as a top predator.…”
Section: Feeding Habitsmentioning
confidence: 99%
See 3 more Smart Citations